2020
DOI: 10.1155/2020/7239075
|View full text |Cite
|
Sign up to set email alerts
|

Improving Efficacy of Endoscopic Diagnosis of Early Gastric Cancer: Gaps to Overcome from the Real-World Practice in Vietnam

Abstract: Objective. To identify factors associated with increased proportion of early gastric cancer to total detected gastric cancer among patients undergoing diagnostic esophagogastroduodenoscopy. Methods. A nationwide survey was conducted across 6 central-type and 6 municipal-type Vietnamese hospitals. A questionnaire regarding annual esophagogastroduodenoscopy volume, esophagogastroduodenoscopy preparation, the use of image-enhanced endoscopy, and number of gastric cancer diagnosed in 2018 was sent to each hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The ability to detect early stage cancer during routine medical services is crucial, as it is the key to reducing gastric cancer-related mortality and improving patient survival times. Many factors can influence the diagnosis of early gastric cancer, including routine preparation before examination, type of endoscopy, use of image-enhanced endoscopy, procedure time, and alertness of endoscopists to early gastric cancer [ 26 28 ]. To reduce missed diagnoses, observation of the cardia subsite should be strengthened during endoscopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to detect early stage cancer during routine medical services is crucial, as it is the key to reducing gastric cancer-related mortality and improving patient survival times. Many factors can influence the diagnosis of early gastric cancer, including routine preparation before examination, type of endoscopy, use of image-enhanced endoscopy, procedure time, and alertness of endoscopists to early gastric cancer [ 26 28 ]. To reduce missed diagnoses, observation of the cardia subsite should be strengthened during endoscopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors associated with the low efficacy of endoscopic diagnosis of EGC in Vietnam included no routine preparation with mucolytic and defoaming agents before EGD and no routine use of IEE during the procedure [12]. In addition, a national multicenter study revealed that EGDs performed at hospitals with an annual EGD volume of < 30,000 or > 60,000 procedures were associated with a lower proportion of EGC detected compared with those performed at hospitals with an annual EGD volume of 30,000-60,000 [12]. These observations could result from the different experiences and workloads of endoscopists.…”
Section: Discussionmentioning
confidence: 99%
“…A high-quality examination during an upper gastrointestinal endoscopy requires optimal mucosal visualization (1,2,15). The use of mucolytic and defoaming agents, such as simethicone and N-acetylcysteine, improves the visibility of gastric mucosa compared to water and is associated with an increased rate of detection of early gastric cancer (15)(16)(17)(18)(19). Recommended in Japanese guidelines on endoscopic diagnosis of EGC but often overlooked in the west, the preparation of the upper gastrointestinal tract with a mucolytic agent 10 to 30 min before endoscopy is an inexpensive method, with a low frequency of adverse reactions/minimal patient burden, that can help obtain the optimal gastric cleanliness (1,15,20,21).…”
Section: Preparation Of the Upper Digestive Tract Before Endoscopymentioning
confidence: 99%